Nephrotic-range proteinuria in a 53-year-old female with thin basement membrane nephropathy: A case report with literature review - Ahmad Matarneh; Sundus Sardar; Pankhuri Mohan; Omar Salameh; Catherine Abendroth; Ronald Miller; Nasrollah Ghahramani; Navin Verma (SAGE Open Medical Case Reports)
Thin basement membrane nephropathy is traditionally characterized by persistent microscopic hematuria and minimal proteinuria, and has long been considered a benign condition. However, emerging evidence challenges this view, as thin basement membrane nephropathy can occasionally present with nephrotic-range proteinuria. We report a case of a 53-year-old female with isolated nephrotic-range proteinuria, ultimately diagnosed with thin basement membrane nephropathy based on electron microscopy findings. Her proteinuria improved significantly over a 10-month period with angiotensin-converting enzyme inhibitor therapy, lisinopril 40 mg once daily. This case adds to the growing recognition that thin basement membrane nephropathy may not always follow a benign course and highlights the importance of careful evaluation and management when clinical features fall outside the expected pattern. A comprehensive literature review is also provided, summarizing similar presentations and management strategies.